Tinjauan Teoretis Makna Arsitektur melalui Perspektif Semiotika - La Ode Amrul Hasan; Ikaputra Ikaputra (Universitas Sebelas Maret Surakarta, 2025)
This study examines the meaning of architecture through a semiotic approach, analyzing architectural elements such as façades, ornaments, spatial arrangements, and materials as signs that communicate messages to society. The goal of this research is to explore the relationship between the physical elements of a building (signifiers) and the meanings they convey (signified) within cultural and social contexts. The methodology involves a literature review focused on interpreting symbols, forms, spaces, and materials in architectural design. The results show that architectural meaning is shaped by cultural and social contexts, with design elements reflecting identity, function, and values accepted by users. This research highlights the role of architecture as a dynamic medium of communication, offering new insights into how architectural meanings are constructed and interpreted through the signs embedded in design elements. It broadens the understanding of architecture not only as a physical structure but also as a cultural and ideological expression.